Monitoring physical and cognitive overload during a training camp in professional female cyclists - Decroix, L.; Piacentini, M. F.; Rietjens, G.; Meeusen, R. (International Journal of Sports Physiology and Performance, 2016)
Purpose: High training loads combined with other stressors can lead to performance decrements. The time needed to recover determines the diagnosis of (non)-functional overreaching or the overtraining syndrome. The aim of this study was to describe the effects of an 8-day (intensified) training camp of professional female cyclists on physical and cognitive performance. Methods: Nine subjects performed a 30-min time trial (TT), cognitive test, and Profile of Mood States questionnaire before, during, and after a training camp (49% increased training volume). On data collection, cyclists were classified as "overreached" (OR) or "adapted" (A) based on TT performance. Two-way repeated-measures analysis of variance was used to detect changes in physical and cognitive parameters. Results: Five cyclists were described as OR based on decreased mean power output (MPO) (-7.03%) on day 8. Four cyclists were classified as A (increased MPO: +1.72%). MPO and maximal heart rate were significantly different between A and OR groups. A significant slower reaction time (RT) (+3.35%) was found in OR subjects, whereas RT decreased (-4.59%) in A subjects. The change in MPO was negatively correlated with change in RT in the cognitive test (R2 = .52). Conclusions: This study showed that the use of objective, inexpensive, and easy-to-interpret physical and cognitive tests can facilitate the monitoring of training adaptations in professional female athletes.